Connecting - Helen Walker; Andrew Statum; Vic Kryston; Jie Li; Dominique Zino; Joonna Smitherman Trapp (Journal of the Assembly for Expanded Perspectives on Learning, 2009)
Connecting - Helen Walker Andrew Statum - The Question Vic Kryston -Conflict Resolution Jie Li - Teaching with Accent Dominique Zino - Space Joonna Smitherman Trapp - Composition Class 7:45 AM